Generalized essential telangiectasia treated with PDL. (16th January 2021) - Powell, Emily; Markus, Ramsey; Malone, Cedar H.
Abstract: Generalized essential telangiectasia (GET) is a rare, clinically benign condition but a source of cosmetic concern for affected patients. There is a dearth of publications and known treatment options for GET. This case report reviews the clinical course of a 54‐year‐old woman who presented with a long‐standing history of telangiectatic patches on her dorsal feet and ankles with progressive spread to the lower extremities consistent with GET. The patient proceeded with two pulsed dye laser (PDL) treatments and had complete resolution of her skin findings maintained at her 1.5‐year follow‐up appointment.